Enforcing periodic secondary structures in hybrid peptides: a novel hybrid foldamer containing periodic gamma-turn motifs - Baruah, Pranjal K.; Sreedevi, N. K.; Gonnade, Rajesh G.; Ravindranathan, Sapna; Damodaran, Krishnan; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2007)
{This note describes the design, synthesis, and conformational studies of a novel hybrid foldamer that adopts a definite compact, three-dimensional structure determined by a combined effect of the special conformational properties of the foldamer constituents. The striking feature of this de novo designed foldamer is its ability to display periodic gamma-turn conformations stabilized by intramolecular hydrogen bonds. Conformational investigations by single-crystal X-ray studies, solution-state NMR, and ab initio MO theory at the HF/6-31G*
Keywords: ammonia-TPD; benzylation reaction; Ce-Al-MCM-41; Friedel-Crafts alkylation; pyridine-FrIR